A platform for Bioengineering Tissue Membranes from cell spheroids - Quang Bach Le; Hariharan Ezhilarasu; Weng Wan Chan; Alok Tanala Patra; Priya Murugan; Shashaank Abhinav Venkatesh; Yean Kai Tay; Shin Ru Lim; Ahmad Amirul Abdul Rahim; Jia Sheng Zach Lee; Xuezhi Bi; Deepak Choudhury (Materials Today Bio)
Cell spheroids are essential building blocks for engineering tissues like cartilage, bone, liver, cardiac, pancreatic, and neural tissues, but controlling their fusion and organisation is challenging. Spheroids tend to fuse into a larger mass, impeding nutrient and waste diffusion. To overcome this, we developed a method to assemble spheroids into a thin layer by using two mesh scaffolds to spread them evenly, and a solid frame with grid to secure the assembly. This allows the spheroids to fuse into a thin membrane-like tissue, allowing better medium diffusion during cell culture. We demonstrated this method by producing cartilage tissue membranes from human mesenchymal stem cell spheroids undergoing chondrogenic differentiation, evaluating spheroid sizes, assembly timing, fusion process and membrane thickness. Our method is a versatile platform for producing tissue membranes from cell spheroids, with significant potential in tissue engineering for creating functional tissue constructs from various cell types.